Konsep Mura Dalam Anime Kasajizou - Zaki Ainul Fadli (Diponegoro University, 2019)
(Title: “Mura ” Concept in Kasajizou Anime) This article aims to uncover the concept of mura in the Kasajizou anime. Mura is one of the traditional Japanese systems, besides ie and kuni. The research method used is the literary sociology approach, namely by revealing one of the anime’s structures (mura ’background) in the anime and relating it to